2022
DOI: 10.1111/andr.13342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes mellitus on sperm quality and fertility outcomes: Clinical evidence

Abstract: Background: Diabetes mellitus is a global epidemic characterized by high morbidity and mortality. Diabetes mellitus can lead to acute and chronic systemic complications.Among them, a negative effect of diabetes mellitus on sperm quality and male/couple fertility has been suggested. However, available studies in diabetes mellitus men evaluated relatively small cohorts with discordant results.Objectives: To evaluate the clinical evidences of the effects of diabetes mellitus on sperm quality and fertility outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 81 publications
0
9
0
1
Order By: Relevance
“…In contrast with the evidence on the hormonal and sexual adverse effects of DM, that on the impact of this highly prevalent chronic disease on fertility is much less consistent. Lotti et al extensively reviewed the clinical studies, which report the relationship among DM, sperm quality, and fertility outcomes, 21 pointing out not only the adverse effect of DM on fertility but also the increased risk of diabetes among childless men.…”
Section: Diabetic Metabolic Dysregulation and Male Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the evidence on the hormonal and sexual adverse effects of DM, that on the impact of this highly prevalent chronic disease on fertility is much less consistent. Lotti et al extensively reviewed the clinical studies, which report the relationship among DM, sperm quality, and fertility outcomes, 21 pointing out not only the adverse effect of DM on fertility but also the increased risk of diabetes among childless men.…”
Section: Diabetic Metabolic Dysregulation and Male Infertilitymentioning
confidence: 99%
“…Lotti et al. extensively reviewed the clinical studies, which report the relationship among DM, sperm quality, and fertility outcomes, 21 pointing out not only the adverse effect of DM on fertility but also the increased risk of diabetes among childless men.…”
Section: Diabetic Metabolic Dysregulation and Male Infertilitymentioning
confidence: 99%
“…However, some studies have reported that the prevalence of infertility in males with DM ranges from approximately 35%-51%. DM in males appears to exert a discernible adverse impact on the fertility of couples, wherein the status of being childless or subfertile in males may be associated with an elevated risk of developing DM ( 9 ). Recent studies have brought to light a substantial correlation between DM and sexual dysfunctions ( 3 , 10 ), specifically, erectile ( 3 , 11 ) and ejaculatory dysfunctions ( 12 ) as well as hypogonadism ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have brought to light a substantial correlation between DM and sexual dysfunctions ( 3 , 10 ), specifically, erectile ( 3 , 11 ) and ejaculatory dysfunctions ( 12 ) as well as hypogonadism ( 11 ). Available data underscores the evident roles that DM plays in impairing male reproductive organs, thereby influencing overall couple fertility ( 9 , 13 ). Therefore, it is well known that the low fertility rate of DM patients in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 DM has been found to contribute to significant alterations in male gonadal physiology in both experimental models and clinical cases [2]. According to meta-analyses conducted on studies focusing exclusively on men with type 1 DM, there is evidence supporting a detrimental effect of diabetes on sperm motility [5]. Type 1 DM individuals exhibit a significantly higher prevalence of immaturity-and apoptosis-related defects in spermatozoa compared to the control group, suggesting an association with impaired spermatogenesis that could potentially impact male fertility [6].…”
Section: Introductionmentioning
confidence: 99%